Feeding behavior in goats in a controlled grazing system of natural succession in tropical dry forest - Rua Bustamante, Clara Viviana; Tarazona, Ariel (Spei Domus, 2023)
Introduction: Goats are selected browsing and selective ruminants, in natural conditions they use up to once hours a day for food consumption. The objective of this study was to evaluate the ingestive behavior and other diurnal behaviors in adult female goats. Methodology: Twelve animals were evaluated under a grazing system with the presence of native trees scattered in the low tropics, without introduced grasses and with a supplementation composed of cut grasses and canoe concentrate within the paddock. The observation of the behaviors was carried out for twelve hours a day and a frequency of five in three days, with which 876 observations were obtained per day and 2628 observations in total, climatic variables were taken into account. The information was processed using the Microsoft Excel program and a multiple correspondence analysis was made, using the R statistical package. Results: The consumption behavior in grazing was presented with a higher frequency during the day (26.4 %), decreasing among the 6:00 a.m. to 9:00 a.m., where high precipitation was evidenced and at 11:00 and 16:00 by canoe supplementation. The browsing behavior was presented in 8.95%, with less frequency in the hours between 9:00 a.m. to 2:00 p.m. Quiet and rumination behavior in the lateral ulna position represented 20.4% and 11.5% respectively, both observed throughout the day. Behaviors such as sleeping, drinking and consuming salt, presented very low frequencies. Conclusions: Goats present a constant ingestive behavior during the hours of the day evaluated.